Centrin-Deleted Leishmania donovani Parasites Help CD4+ T Cells to Acquire Th1 Phenotype and Multi-Functionality Through Downregulation of CD200–CD200R Immune Inhibitory Axis - Singh, Rakesh K.; Gannavaram, Sreenivas; Ismail, Nevien; Kaul, Amit; Gedda, Mallikarjuna Rao; Nakhasi, Hira L. (Frontiers in Immunology, 2018)
The protozoan parasite Leishmania has evolved several strategies to undermine host defense mechanisms by inducing Th2 type adaptive immunity and suppressing effector functions of Th1 phenotype. In our earlier studies using centrin gene deleted Leishmania (LdCen-/-) parasites as an immunogen, we have shown induction of an effective Th1 type immunity and robust memory responses that mediate protection against virulent challenge. However, role of inhibitory signals in Leishmania vaccine induced immunity in general and LdCen-/- in particular has not been studied. Herein we report that immunization with LdCen-/- parasites produces more functional Th1 type CD4+ T cells via down regulation of CD200-CD200R immune inhibitory axis compared to wild type infection. We found that expression of CD200 and CD200R was significantly reduced in LdCen-/- infection compared to wild type infection. Diminished CD200-CD200R signaling in LdCen-/- infection enabled proliferation of CD4+ T cells and resulted in the induction of pro-inflammatory cytokines, and suppression of anti-inflammatory response. The effects of diminished CD200-CD200R signaling by LdCen-/- were most evident in the suppression of IL-10 producing CD4+ T cells that helped enhance more Th1 cytokine producing and multi-functional T cells compared to wild type infection. In vivo blocking of CD200 expression with anti-CD200 treatment in wild type infected mice limited Th2 response as indicated by reduction of IL-10 producing Tr1 cells and reduced parasite burden. On the other hand treatment with anti-CD200 improved the LdCen-/- vaccine induced multifunctional response and reduction in splenic parasite load upon challenge. Taken together, these studies demonstrate the role of CD200-CD200R signals in the protection induced by LdCen-/- parasites.